Transformasi Keuangan Digital dalam Perspektif Ekonomi Syariah : Peluang, Tantangan, dan Dampak Terhadap Inklusi Keuangan - Ceasario, Adrian Fadel; Fauzatul Laily Nisa (Al Rikaz: Jurnal Ekonomi Syariah, 2024)
This study discusses digital transformation, encompassing opportunities, challenges, and its impact on Sharia-based financial inclusion in Indonesia. With the advancement of digital technology, Islamic financial services have the potential to reach a broader population and enhance efficiency and transparency. Digital transformation enables communities in remote areas to easily access Islamic banking and financial services through digital platforms such as e-wallets, mobile banking, and Islamic fintech applications. This study employs a descriptive approach, utilizing data from references, previous research literature, books, reports, and other sources. The study concludes that to enhance Islamic financial inclusion, collaboration among the government, financial institutions, and technology developers is essential to create an ecosystem that supports the growth of Islamic fintech. Additionally, increasing financial literacy through structured educational programs is crucial. Digital transformation has proven to be one of the best methods for expanding Islamic financial inclusion, bringing greater economic and social benefits to the Indonesian society.